A New Method for the Synthesis of 3-Substituted Indoles - Natarajan, Rakesh; Rappai, John P.; Unnikrishnan, Peruparampil A.; Radhamani, Sandhya; Prathapan, Sreedharan (Synlett, 2015)
Starting from readily accessible nitrones and electron-deficient acetylenes, a highly efficient and versatile synthetic protocol for 3-substituted indoles has been developed.
Keywords: indoles; nitrones; electron-deficient acetylenes; nucleophilic addition; 1,3-dipolar additions